Role of Exosome in Solid Cancer Progression and Its Potential Therapeutics in Cancer Treatment - Nada Aakel; Rawdhah Mohammed; Aseela Fathima; Rabia Kerzabi; Atiyeh Abdallah; Wisam Nabeel Ibrahim (Cancer Medicine, 2025)
ABSTRACT Background Exosomes are extracellular vesicles ranging from 40 to 100 nm in diameter that mediate intercellular communication by transferring proteins, lipids, nucleic acids, and other metabolites. In the context of cancer, exosomes influence the tumor microenvironment by carrying regulatory RNAs such as miRNA, circRNA, and lncRNA. They originate from various cells, including adipocytes, fibroblasts, and hepatocellular carcinoma (HCC) cells, and can either promote or inhibit cancer progression through pathways like MAPK and PI3K‐Akt. Aim This review aims to explore the role of exosomes in the progression of solid cancers, emphasizing their self‐induced activation mechanisms and how they modulate tumor behavior. Methodology A comprehensive review of recent literature was conducted, focusing on studies that investigated the biological functions of exosomes in solid tumor progression, including their molecular cargo, cellular origin, and involvement in signaling pathways. Results Findings from multiple studies indicate that cancer‐derived exosomes contribute to tumor proliferation, metastasis, and therapy resistance by enhancing communication within the tumor microenvironment. These vesicles activate oncogenic pathways and can serve as biomarkers or therapeutic targets due to their role in disease modulation. Conclusion Exosomes play a pivotal role in solid cancer progression and offer significant potential in advancing our understanding of tumor biology. Their capacity to influence key signaling pathways and facilitate intercellular communication makes them promising candidates for novel diagnostic and therapeutic strategies.